Circulating Tumor Cells as a Novel Prostate Cancer Diagnostic Tool - Fatemeh Khatami (Urology Research Center, 2020)
The current screening test for prostate cancer (PCa) has the weak point of a high false-negative rate and a low true positive rate. There is an extreme need for a new and accurate testing system. Circulating Tumor Cells (CTCs) as the main liquid biopsy components provide excellent biomarkers for early diagnosis of PCa, prognosis, recurrence risk, and treatment efficacy. These tumor cells can get the release of tumor and freely circulate in the patient’s body fluids and easily are traceable to answer the presence of the tumor more than its stage. The new gifted ISET®-CTC Test is a simple blood test with high sensitivity and specificity for the detection of CTC in PCa. As a novel idea, it is a challengeable point nowadays that it needs further studies.